A Comparative Study between Quantum Mechanics and Yogācāra Buddhism on Properties of Material Objects - Chen, Ven. Hui (The Journal of International Association of Buddhist Universities (JIABU), 2018)
With the development of quantum mechanics, the knowledge of properties of material objects have been greatly changed, quite different from what people have taken for granted as well as that in classical physics. Since Yogācāra is considered to be one of most compatible Buddhist theories with modern science, in order to see exactly how close Yogācāra is to quantum mechanics, this article aims at comparing quantum mechanics and Yogācāra on properties of material objects from three aspects, the source of material objects, their substantiality, and the interference from the mind. By doing this, a conclusion is made that the two have the same opinions at a general level but different, to certain extents, from each other at a specific level.